Risk and Capital Flight in Developing Countries. (IMF Working Papers; Working Paper ;, 1990)
The risks of large capital losses on the domestic assets of developing countries resulting from expropriation, inflation, or devaluations are identified as the major causes of capital flight. The combination of large foreign loans and capital flight from developing countries during the 1970s and early 1980s reflected different perceptions of domestic residents and foreign lenders regarding the risks of holding domestic assets. However, the debt crisis reduced these differences in perceived risks, and resulted in a decline of foreign loans coupled with continuation of capital flight. If sound macroeconomic and structural policies can reduce those risks, they can also stem capital flight.